A method to evaluate body length of live aquatic vertebrates using digital images. Issue 10 (5th April 2021) - Arismendi, Ivan; Bury, Gwen; Zatkos, Lauren; Snyder, Jeff; Lindley, David
Abstract: Traditional methods to measure body lengths of aquatic vertebrates rely on anesthetics, and extended handling times. These procedures can increase stress, potentially affecting the animal's welfare after its release. We developed a simple procedure using digital images to estimate body lengths of coastal cutthroat trout ( Oncorhynchus clarkii clarkii ) and larval coastal giant salamander ( Dicamptodon tenebrosus ). Images were postprocessed using ImageJ2. We measured more than 900 individuals of these two species from 200 pool habitats along 9.6 river kilometers. The percent error (mean ± SE) of our approach compared to the use of a traditional graded measuring board was relatively small for all length metrics of the two species. Total length of trout was −2.2% ± 1.0. Snout–vent length and total length of larval salamanders was 3.5% ± 3.3 and −0.6% ± 1.7, respectively. We cross‐validated our results by two independent observers that followed our protocol to measure the same animals and found no significant differences ( p > .7) in body size distributions for all length metrics of the two species. Our procedure provides reliable information of body size reducing stress and handling time in the field. The method is transferable across taxa and the inclusion of multiple animals per image increases sampling efficiency with stored images that can be reviewed multiple times. This practical tool can improve data collection of animal size over large sampling efforts and broad spatiotemporal contexts. Abstract : We developed a procedure to estimate body length of aquatic vertebrates using digital images of live animals in the field and post processing using ImageJ2. This method is reliable and reduces stress and handling time in the field. This tool can improve our understanding about species responses to disturbances over large sampling efforts and broader spatiotemporal contexts.